Potable Water Fluoride Rapid Detection Based on TBAF Desilylation by a Novel Fluorogenic 7-O-tert-butyldimethylsilyl-3-cyano-4-methylcoumarin Compound - Akumu, Edwin Otieno; Barasa, Stephen; Lutta, Samwel; Akeng’a, Teresa A. (African Journal of Education,Science and Technology (AJEST), 2021)
This article reports the synthesis and properties of a novel fluoride detector, 7-O-tertbutyldimethylsilyl-3-cyano-4-methylcoumarin, which emits a lavender blue fluorescence in aqueous solution when fluoride ions are present. Bk-F93 F2000 Fluorospectrophotometer (FS), MRC-UV-Vis Spectrophotometer-UV-(11S/N; UEB1011006), GC micromass spectrometer (Micromass, Wythenshawe, Waters, Inc. UK), and Bruker Avance NEO 500 MHz (TXO cryogenic probe) NMR spectrometers were used for the spectral study. MestreNova (v14.0.0) program was used to process the NMR spectra. This sensor is highly specific and sensitive to water - soluble fluoride. The findings also show that fluoride doses as minimal as 0.18 μM (3.42 x1011 mgL-1) can be reliably measured almost immediately, as shown by 2nd order rate constant of 1.9 x10 M-1min-1, in comparison to most fluoride sensors' range of 0.54 - 116M-1min-1. The synthetic compound's responsiveness as a fluoride probe in the presence of other competing anions indicated no direct detection interference by any of evaluated ionic species. This fluoride probe demonstrated a higher quantum yield than the selected standard (quinine sulfphate), with values of Ф = 0.65 and Ф = 0.54, respectively. Fluoride screening with 7-O-tertbutyldimethylsilyl-3-cyano-4-methylcoumarin is simple and fast compared to conventional approaches that involve professional staff. As a result, the approach outlined herein is applicable and incredibly useful for assessing the quality of potable water in communities.